Nurses' perceptions of high‐alert medication administration safety: A qualitative descriptive study. (5th September 2019) - Sessions, Laura C.; Nemeth, Lynne S.; Catchpole, Kenneth; Kelechi, Teresa J.
Abstract: Aims: The aim of this study was to determine nurses' perceptions of supports and barriers to high‐alert medication (HAM) administration safety. Design: A qualitative descriptive design was used. Methods: Eighteen acute care nurses were interviewed about HAM administration practices. Registered nurses (RNs) working with acutely ill adults in two hospitals participated in one‐on‐one interviews from July–September, 2017. Content analysis was conducted for data analysis. Results: Three themes contributed to HAM administration safety: Organizational Culture of Safety, Collaboration, and RN Competence and Engagement. Error factors included distractions, workload and acuity. Work arounds bypassing bar code scanning and independent double check procedures were common. Findings highlighted the importance of intra‐ and interprofessional collaboration, nurse engagement and incorporating the patient in HAM safety. Conclusions: Current HAM safety strategies are not consistently used. An organizational culture that supports collaboration, education on safe HAM practices, pragmatic HAM policies and enhanced technology are recommended to prevent HAM errors. Impact: Hospitals incorporating these findings could reduce HAM errors. Research on nurse engagement, intra‐ and interprofessional collaboration and inclusion of patients in HAM safety strategies is needed. Abstract : 目的: 本研究的目的在于确定护士对高危药品(HAM)用药安全有利因素及障碍的看法。 设计: 采用了定性描述设计 方法: 就高危药品(HAM)用药实践采访了18名急症护理护士。2017年七月至九月, 对两家医院护理重症成年患者的注册护士(RN)进行了一对一访问。内容分析用于数据分析。 结果: 三个有助于高危药品(HAM)用药安全的主题:组织安全教育、合作、注册护士能力以及参与度。过失原因包括各种干扰、工作量以及敏锐度。绕过条形码扫描和独立复查程序的行为十分常见。调查结果强调了专业内和跨专业合作、护士参与度、以及让患者加入高危药品(HAM)安全。 结论: 目前并未贯彻高危药品(HAM)安全策略。建议建立支持合作的组织教育、高危药品(HAM)安全实践教育、高危药品(HAM)实用政策并提高技术避免高危药品(HAM)过失。 影响: 采纳这些调查结果的医院能够减少高危药品(HAM)过失。需要对护士参与度、专业内和跨专业合作以及让患者加入高危药品(HAM)安全策略进行研究。